Prognostic factors in head and neck mucoepidermoid carcinoma: experience at a single institution based on 64 consecutive patients over a 28-year period. Issue 3 (March 2018) - Granic, M.; Suton, P.; Mueller, D.; Cvrljevic, I.; Luksic, I.
Abstract: Mucoepidermoid carcinoma (MEC) is the most common malignancy of the salivary glands. The clinical behaviour of MEC is largely unpredictable, ranging from indolent tumour growth to highly aggressive metastatic spread. The objective of this study was to determine the clinicopathological predictors of recurrence and survival in patients with head and neck MEC. The medical records of 64 patients who underwent surgical treatment for head and neck MEC between 1982 and 2010 were reviewed. The main outcome measures were disease-free survival (DFS) and overall survival (OS). Clinicopathological parameters evaluated were age, sex, anatomical subsite, histological grade, tumour stage, tumour size, adjuvant therapy, and nodal and margin status. For the entire cohort, the 5-year DFS was 82.8% and the 5-year OS was 67.2%. Histological grade and tumour subsite were statistically significant predictors of OS. Furthermore, tumour stage and nodal status were statistically significant predictors with respect to OS. Advanced tumour stage, high histological grade, submandibular/sublingual localization, and positive nodal status were independent predictors of the prognosis in patients with head and neck MEC. Further studies into the molecular biology of MEC are needed in order to provide new therapeutic strategies for patients with locally aggressive and highly metastatic carcinomas.